Group A streptococci infection. A systematic clinical review exemplified by cases from an obstetric department. (August 2017) - Gustafson, Line Winther; Blaakær, Jan; Helmig, Rikke Bek
Abstract: Group A streptococci infection has re-emerged since the 1980s and onward, despite the awareness of the etiology and the use of penicillin. It now accounts for more than 75, 000 deaths worldwide every year. Postpartum women have a 20-fold increased incidence of group A streptococci disease compared to non-pregnant women. This review focuses on the epidemiology, pathophysiology, clinical presentation, prevention and treatment of group A streptococcal infection in pregnancy. Search strategy: We searched the following electronic databases from 1980–March 2016: PubMed-Medline, Embase, SveMed+, Bibliotek.dk, Cinahl and Cochrane database using following MESH terms or Emtree terms; (Fasciitis, Necrotizing), Soft Tissue Infection, Streptococcus Pyogenes, Postpartum Period, Pregnancy, (Shock, Septic), Microbiology, Epidemiology, Disease Management. We identified 439 records. After literature screening we ended up with 66 records. Group A streptococci infection, and in particular streptococcal toxic shock syndrome and necrotizing fasciitis, can be life threatening. Despite advanced surgery, antibiotics and supportive therapy, there is still a high mortality associated with these infections. The clinical picture can vary greatly and awareness of the condition and its ability to progress rapidly is crucial for prompt treatment. A profound review on the subject is presented in the paper.